The effects of the Pendulum distalising appliance and cervical headgear on the dentofacial structures - Toy Ebubekir; Enacar Ayhan (Sciendo, 2011)
Background: Headgears are effective in distalising maxillary molars, but success depends on patient compliance and tolerance. Intra-oral distalising appliances are simple to construct and use and may be a better alternative for patients who are non-compliant or cannot tolerate headgear.